1998
DOI: 10.1001/archpsyc.55.5.393
|View full text |Cite
|
Sign up to set email alerts
|

Violence by People Discharged From Acute Psychiatric Inpatient Facilities and by Others in the Same Neighborhoods

Abstract: "Discharged mental patients" do not form a homogeneous group in relation to violence in the community. The prevalence of community violence by people discharged from acute psychiatric facilities varies considerably according to diagnosis and, particularly, co-occurring substance abuse diagnosis or symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

54
918
8
36

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,311 publications
(1,016 citation statements)
references
References 20 publications
54
918
8
36
Order By: Relevance
“…This combination is a strong predictor of recidivism. 153 Mentally ill inmates also reported longer criminal histories than other inmates. 154 More than half (52 percent) reported three or more prior offenses.…”
Section: Treatment Is Cost-effectivementioning
confidence: 99%
“…This combination is a strong predictor of recidivism. 153 Mentally ill inmates also reported longer criminal histories than other inmates. 154 More than half (52 percent) reported three or more prior offenses.…”
Section: Treatment Is Cost-effectivementioning
confidence: 99%
“…9 Steadman et al monitored groups of patient who were discharged into the population from general psychiatric hospitals in four cities in the United States. 10 The primary diagnoses included depression (42%), substance abuse (21.8%), schizophrenia (17%), bipolar disorder (14%), personality disorder (2%) and general psychotic disorders (3%). The authors reported that, during the first year after discharge, 27.5% of the patients committed at least one violent act that resulted in the victim requiring medical attention.…”
Section: Introductionmentioning
confidence: 99%
“…Although no more prone to violence than the general population, research has shown that when individuals who are mentally ill become violent, family members are most often the victims (Arboleda-Florez, 1998;Steadman et al, 1998;Tardiff, 1984). Parents are the most common victims (Binder & McNeil, 1986;Straznickas, McNeil & Binder, 1993), specifically mothers (Estroff, Zimmer, Lachicotte & Benoit, 1994;Estroff, Swanson, Lachicotte, Swartz & Bolduc 1998;.…”
mentioning
confidence: 99%